Constructing College Academic Resilience Scale: Using Multifactor and Polytomous Rasch Model - Fakhriya, Siti Dini; Darmayanti, Kusumasari Kartika Hima; Meyrinda, Jesyia; Zain, Tsurayya Syarif; Ramadhan, Mawaddah; Lestari, Indah; Liandri, Kenya Janesa; Triyani, Liya; Azzahrah, Annisa Syifa; Afnes, Silvia (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2025)
Academic resilience is crucial for students. It enhances their ability to manage academic difficulties, which underscores its importance in educational settings. This study aims to develop and validate the College Academic Resilience Scale (CARS), which assesses academic resilience in undergraduates. 200 undergraduate students from South Sumatra, Indonesia, were used to analyze using the multifactor confirmatory factor analysis model and the polytomous Rasch model. This measure consists of five dimensions that measure academic resilience, indicating that an overall analysis of items in academic resilience instruments using Rasch modeling has good validity and reliability. Furthermore, more research on measurement validation is needed in diverse cultures and countries.